A review of the evaluation of road accidents and its application to developing countries - Abdul Aziz Abdul Muti, author; University of Newcastle Upon Tyne. Department of Civil Engineering (1980)
Thesis (Master of Science) - University of Newcastle Upon Tyne, 1980